Association of Soluble Klotho Level with Adverse Outcomes in Patients on Maintenance Hemodialysis - Yu, Li-xia (Dis Markers, 2020)
BACKGROUND: The predictive value of soluble Klotho (sKlotho) for adverse outcomes in patients on maintenance hemodialysis (MHD) is controversial. In this study, we aimed to clarify the potential association of sKlotho levels with adverse outcomes in this patient population. MATERIALS: A total of 211 patients on MHD were identified and stratified according to the median sKlotho level. Patients were followed up for adverse outcomes including cardiovascular (CV) morbidity and all-cause mortality. RESULTS: During the 36-month follow-up, 75 patients [51 CV events (including 16 CV deaths) and 40 deaths] experienced adverse outcomes. After stratification according to median sKlotho level, patients with a lower sKlotho level had a greater risk of CV events (38.2% vs. 19.5%, p = 0.006), all-cause mortality (28.4% vs. 11.6%, p = 0.003), and combined adverse outcomes (51.0% vs. 24.2%, p < 0.001). Similar observations were made from analyses using Kaplan-Meier survival curves. Cox regression analysis showed that a low sKlotho level was strongly correlated with CV morbidity [1.942 (1.030–3.661), p = 0.040)], all-cause mortality [2.073 (1.023–4.203), p = 0.043], and combined adverse outcomes [1.818 (1.092–3.026), p = 0.021] in fully adjusted models. CONCLUSIONS: The sKlotho level was an independent predictive factor of adverse outcomes including CV morbidity and mortality in patients on MHD.